Guidelines and regulations for fecal sludge management from on-site sanitation facilities - Jayathilake, Nilanthi; Drechsel, Pay; Keraita, B.; Fernando, Sudarshana; Hanjra, Munir A. (International Water Management Institute, 2019)
In low- and middle-income countries, the management of fecal sludge from on-site sanitation systems has received little attention over many decades, resulting in insufficient or missing regulations to guide investments and management options. To address this gap, this report examines existing and emerging guidelines and regulations for fecal sludge management (FSM) along the sanitation service chain (user interface, containment, emptying, transport, treatment, valorization, reuse or disposal). It also draws empirical examples from guidelines across the globe to support policy-makers, planners, and sanitation and health officers, as well as consultants in low- and middle-income countries in the development and design of local and national FSM guidelines and regulations.